Academic Motivation in English Online Classes: A Comparative Study of Universities in Malaysia and Indonesia - Omar, Suhaida; Shaharuddin, Wan Yusoff Wan; Azim, Nik Ahmad Farhan Azim @ Nik; Nawi, Noor Syamimie Mohd; Zaini, Noraini; Syahfutra, Wandi (Universitas Pendidikan Indonesia, 2021)
This study intended to fill the gap of undergraduates’ academic motivation in Malaysia and Indonesia where, to date, little study has been done. It investigated and compared undergraduates’ academic motivation levels in English online classes in two universities in both countries. Online questionnaires on students’ self-regulated learning (SRL) and self-efficacy towards online learning adapted from Motivated Strategies for Learning Questionnaire (MSLQ) were distributed to 206 undergraduates from University A in Malaysia and 174 undergraduates from University B in Indonesia. Switching from physical traditional to online classes is the new norm that could be challenging and demotivating, but the results showed that the students from both universities achieved mostly high mean scores of the SRL and self-efficacy items. This indicated that their academic motivation levels were high, they were in control over their learning process, and have positive perceptions towards online classes. This uniformity also implied that although English is a second language in Malaysia, and a foreign language in Indonesia, the undergraduates were not affected by their linguistics, and institutional contexts. This study has contributed towards the extension of the current knowledge involving undergraduates’ academic motivation towards learning English online and suggested that teachers could help to strategise students’ SRL and self-efficacy to increase their English language performances, particularly in the pandemic era. Further research could explore the effects of academic motivation on learning outcomes or language performance as this could assist teachers to improve learners’ English proficiency in online classes.